Accepting Diversity from Christian View - Petrus Dori (Eduvest - Journal of Universal Studies, 2022)
Accepting and treating diversity in a friendly manner is essential from a Christian perspective. If nowadays progress is being seen in terms of accepting, respecting and treating each other in a friendly manner, then this cannot be separated from the contribution of faith and religious ethical values adopted by believers. In the context of this paper, the author limits himself to the contribution of the Christian religion. For followers of Christ, being friendly to diversity whether due to physical differences, skin color, social status, gender, ethnicity, religion or culture has historical and intercultural theological aspects.